HUMAN GEOGRAPHY WITH GEOGRAPHICAL INFORMATION SYSTEMS - Sergiy Kostrikov; Kateryna Segida (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The purpose of this paper is to represent  that a GIS in human geography is not only a straightforward tool for generating and spatially analysing maps and graphics, but also is intended to identify certain spatial samples and to form new spatial derivative data for reaching advances in human geography research. Digital maps introduced as a paper map effective alternative made possible by GIS. Once introduced by the authors environmental geography concept is additionally discussed purely of human geography contribution to this field by geographical information systems. Traditional quantitative geography is explained to be a key basic for all following GIS applications in geographic sciences. The conclusion is made this field is highly essential for the further GIS-expansion within human geography. Few examples of original software with respect of city key element extraction are suggested for the urban system analysis.